2019
DOI: 10.1097/rlu.0000000000002424
|View full text |Cite
|
Sign up to set email alerts
|

Initial Versus Follow-up Sequential Myocardial 123I-MIBG Scintigraphy to Discriminate Parkinson Disease From Atypical Parkinsonian Syndromes

Abstract: Purpose Previous single-center or meta-analysis studies analyzed myocardial 123I-metaiodobenzylguanidine (123I-MIBG) scintigraphy in a single image session and demonstrated low sensitivity and high specificity for discriminating Parkinson disease (PD) from atypical Parkinsonian syndromes (APS). This study aimed to assess diagnostic ability of myocardial 123I-MIBG scintigraphy at 2 phases to discriminate PD from APS. Patients and Methods This hospital-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The study demonstrated that sequential 123 I-MIBG scintigraphies may improve the diagnostic ability to discriminate between PD and atypical parkinsonisms. 28 Our findings are in line with the latter observations, since evidence of cardiac sympathetic denervation was found in 80% PD patients with a relatively brief disease course (mean disease duration of 3.5 AE 2.8 years). In terms of specific diagnostic utility, 123 I-MIBG scintigraphy improved the diagnostic accuracy in 22% of our sample.…”
Section: Contribution Of 123 I-mibg Myocardial Scintigraphy To the Diagnostic Processsupporting
confidence: 92%
“…The study demonstrated that sequential 123 I-MIBG scintigraphies may improve the diagnostic ability to discriminate between PD and atypical parkinsonisms. 28 Our findings are in line with the latter observations, since evidence of cardiac sympathetic denervation was found in 80% PD patients with a relatively brief disease course (mean disease duration of 3.5 AE 2.8 years). In terms of specific diagnostic utility, 123 I-MIBG scintigraphy improved the diagnostic accuracy in 22% of our sample.…”
Section: Contribution Of 123 I-mibg Myocardial Scintigraphy To the Diagnostic Processsupporting
confidence: 92%
“…Therefore, I-123 MIBG cardiac scans have been widely used to assess non-invasively the presynaptic cardiac sympathetic nerve endings. Many studies have focused on the differential diagnosis of PD from atypical parkinsonism, such as multiple system atrophy or corticobasal degeneration [9][10][11][12][13][14][15][16][17]. Those studies consistently showed that I-123 MIBG cardiac scans were very useful in distinguishing early PD, and that the heart-to-mediastinal ratio (HMR) was a good diagnostic indicator in discriminating those diseases.…”
Section: Resultsmentioning
confidence: 99%
“…However, further study with a larger population is needed. As mentioned earlier, the normal range of the WR has not yet been determined, and various studies have used various normal ranges [12,22,26,38]. To predict OH in PD patients with a decreased HMR, we obtained the optimal cutoff value of the WR by ROC analysis.…”
Section: Plos Onementioning
confidence: 99%
“…Tracer uptake was measured within each region of interest to calculate the H/M ratio. The lower limit of the reference value for delayed H/M ratio was calculated to be 1.78 12 , 13 . A delayed H/M ratio < 1.78 was defined as abnormal.…”
Section: Methodsmentioning
confidence: 98%
“…Some PD patients have a normal 123 I-MIBG uptake analogous to APS, and this imaging phenotype was previously given the term “scans without evidence of cardiac norepinephrine deficit (SWEND)” 13 . PD patients with SWEND had mild Hoehn and Yahr (H&Y) stage, short disease duration, slow progression of motor dysfunction, a lower incidence of the wearing-off phenomenon, and a lower prevalence of nonmotor symptoms 7 , 10 12 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%